An International Survey of Deep Brain Stimulation Utilization in Asia and Oceania: The DBS Think Tank East - Zhang, Chencheng; Ramirez-Zamora, Adolfo; Meng, Fangang; Lin, Zhengyu; Lai, Yijie; Li, Dianyou; Chang, Jinwoo; Morishita, Takashi; Inoue, Tooru; Fujioka, Shinsuke; Oyama, Genko; Coyne, Terry; et al. (Frontiers in Human Neuroscience, 2020)
Introduction: To evaluate the current utilization and challenges in fully implementing the use of deep brain stimulation (DBS) treatment in Asia and Oceania. Methods: We conducted a medical literature search to identify DBS research performed by investigators with primary affiliation in Asian and Oceania countries between March 1, 2013 and March 1, 2019, followed by an international survey-based study. Additionally, we obtained added information regarding the DBS challenges and opportunities from the technology/industry perspective within China and Japan. We also described the current situation of DBS in India. Results: Most publications (390/494; 78.95%) in English language originated from East Asia. In West Asia, Turkey, Israel, and Iran accounted for most DBS publications. We found no publications from the remaining 35 Asian countries. Lack of community referrals to tertiary centers was identified as the most common limitation for the widespread use of DBS in Asia (68.97%). In China, despite an increasing number of centers performing DBS surgeries, most of them accomplished less than 10 cases per year. In contrast, the number of DBS cases in Japan has been decreasing. Centers offering DBS surgeries as well as corresponding fellowship training in India are limited. Conclusion: Appropriate referrals, access, infrastructure, and the presence of full multidisciplinary DBS teams are common limitations of DBS in Asia. Most centers in China, Japan, and India performed less than 10 cases per year and a future study is expected to address the impact on quality in centers performing such few cases.